2001
DOI: 10.1590/s0103-50532001000400005
|View full text |Cite
|
Sign up to set email alerts
|

Solution and solid state thermal stability of morpholinedithiocarbamates

Abstract: Estudos termogravimétricos e calorimétricos diferenciais de morfolinoditiocarbamatos de NH 4 + , Mn 2+ , Co 2+ , Ni 2+ e Cu 2+ foram realizados em atmosferas de ar e nitrogênio, para avaliar a influência da presença do oxigênio como heteroátomo no anel da amina na decomposição térmica. Produtos de decomposicão térmica foram caracterizados através de difratogramas de raios X, sendo predominantemente formados por sulfetos metálicos, sob atmosfera dinâmica de nitrogênio e óxidos metálicos, sob ar. Usando espectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
0
10
0
1
Order By: Relevance
“…91 This is in total agreement with our previous findings for other cyclic DTC complexes with the same metal cations. 24,25,90 The characteristic C-N stretching vibrational mode is observed at 1474-1503 cm -1 and is less intense than that observed for alkyl DTC derivatives due to the low double bond character caused by the rigid ring system. 92 Table 1.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…91 This is in total agreement with our previous findings for other cyclic DTC complexes with the same metal cations. 24,25,90 The characteristic C-N stretching vibrational mode is observed at 1474-1503 cm -1 and is less intense than that observed for alkyl DTC derivatives due to the low double bond character caused by the rigid ring system. 92 Table 1.…”
Section: Resultsmentioning
confidence: 91%
“…The limiting half life (t 1/2lim ) suggests that hex is more stable than piperidinedithiocarbamate (pip) and morpholinedithiocarbamate (mor) and much less stable than pyrrolidinedithiocarbamate (pyr). 23,90 The thermal analytical studies revealed that sulfides were the main residues obtained under nitrogen atmosphere, which were reduced to the elementary metals in the case of the copper(II) and zinc(II) complexes. Oxysulfates were observed in air as intermediates of the decomposition of Ni(hex) 2 , Cu(hex) 2 and Cd(hex) 2 , while oxides were obtained as final decomposition products.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 Os sais de sódio e potássio são costumeiramente usados na preparação de complexos de ditiocarbamatos com íons metálicos, cujo comportamento térmico foi descrito previamente. [17][18][19][20][21][22][23] Considerando a relevância e os poucos dados descritos na literatura, o presente trabalho trata da síntese e caracterização, assim como do estudo termoanalí-ticos envolvendo TG/DTG e DSC de sais de Na[S 2 CNR] e K[S 2 CNR] derivados de aminas cíclicas (R = pirrolidina (pyr), piperidina (pip), morfolina (mor), hexametileno (hex)), em atmosfera de ar.…”
Section: Introductionunclassified